EFFECT OF ATORVASTATIN AND ROSUVASTATIN ON QUORUM SENSING, BIOFILM FORMATION AND BACTERIAL MOTILITIES OF PSEUDOMONAS AERUGINOSA - SAJAL SARABHAI; LOVEDEEP KAUR DHALIWAL; NEENA CAPALASH; PRINCE SHARMA (International Journal of Pharma and Bio Sciences, 2015)
Statins have been widely studied as antibacterial compounds, but the mechanism of their bacterial inhibition is still not known. In the present investigation two statins, atorvastatin and rosuvastatin, were tested for their antimicrobial activity against Pseudomonas aeruginosa and both showed MIC of 625μg/ml. Both the statins shared structural similarity with quorum sensing signal molecule of Gram negative bacteria i.e. N-acylhomoserine lactone (AHL) but showed no functional agonist or antagonist activity, as indicated by QS-deficient Agrobacterium tumefaciens A136 biosensor strain. Atorvastatin increased the flagella-mediated swarming, swimming and type IV pili-mediated twitching motilities and biofilm formation in P. aeruginosa PAO1 while rosuvastatin decreased all three motilities slightly but had no effect on biofilm formation.